2013
DOI: 10.1080/19476337.2013.834977
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and changes in cell morphology ofEscherichia coliO157:H7 in liquid medium and skim milk in the presence of caffeine

Abstract: Behavior and changes in cell morphology of Escherichia coli O157:H7 in liquid medium and skim milk in the presence of caffeine Comportamiento y cambios en la morfología celular de Escherichia coli O157:H7 en un medio líquido y en leche descremada en presencia de cafeína The objective of this study was to investigate the antibacterial effect of caffeine on the behavior and changes in cell morphology of E. coli O157:H7 in a liquid medium and in skim milk. The inhibitory effect of caffeine at different concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In other studies, caffeine was able to decrease the minimum inhibitory concentration (MIC) values of gentamicin against S. aureus and P. aeruginosa [20, 21]. Previously, the antimicrobial properties of caffeine against Candida albicans were demonstrated [22, 23]. Based on the above, the aim of the present study was to evaluate the antibacterial activities of caffeine, green tea extract, EGC, and EGCG alone and in combination with gentamicin against two clinically important bacteria, S. aureus and P. aeruginosa .…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, caffeine was able to decrease the minimum inhibitory concentration (MIC) values of gentamicin against S. aureus and P. aeruginosa [20, 21]. Previously, the antimicrobial properties of caffeine against Candida albicans were demonstrated [22, 23]. Based on the above, the aim of the present study was to evaluate the antibacterial activities of caffeine, green tea extract, EGC, and EGCG alone and in combination with gentamicin against two clinically important bacteria, S. aureus and P. aeruginosa .…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine is also contained in coffee, tea, chocolate, and many other food sources like cola and is used by many students as a stimulant [7,8]. Even though the physiological mechanisms of caffeine are not well understood, caffeine beneficially affects performance by reducing the perception of fatigue, enhancing central drive, and/or improving exercise capability [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was confirmed that caffeine was able to decrease the MIC values of gentamicin against S. aureus and P. aeruginosa [ 14 , 15 ]. Additionally, the antimicrobial properties of caffeine against Candida albicans were reported [ 16 , 17 ]. Different mechanisms have been mentioned about antibacterial activity of caffeine such as inhibiting incorporation of adenine and thymidine in the synthesis of DNA via inhibition of thymidine kinase and also inhibiting the synthesis of DNA [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%